Crystal rigidifying strategy toward hybrid cadmium halide to achieve highly efficient and narrowband blue light emission. (June 2022) - Zhao, Jian-Qiang; Ge, Hui; Wu, Yu-Fang; Xu, Wen-Jie; Xu, Kai; Ma, Jia-Qian; Yang, Qian-Lu; Yue, Cheng-Yang; Lei, Xiao-Wu
Abstract: Highly efficient and narrowband blue light-emitting performance is extremely crucial for the optoelectronic applications of organic-inorganic hybrid perovskites. However, the not yet viable approach has been shown to simultaneously improve photoluminescence quantum yield (PLQY) and narrow linewidth of blue light emission. Herein, a new crystal rigidifying strategy is proposed as a viable dual-optimization avenue. Specifically, we perform a post-synthetic technique on hybrid cadmium halides and successfully convert zero-dimensional (0D) DMP-0-CdBr4 to one-dimensional (1D) DMP-1-CdBr3, accompanied by luminescent transformation from sky-blue (470 nm) to deep-blue (432 nm) emissions. The structural evolution from discrete block to infinite chain significantly enhances the crystal rigidity, which results in narrower emission linewidth (89 to 50 nm) and increased color purity (74.5% to 96.7%). Synchronously, the PLQY also realizes a notable enhancement from 14.0% to 52.3%. Systematical characterizations demonstrate that enhanced crystal rigidity simultaneously weakens the electron-phonon interaction and slows down nonradiative decay, which narrows the emission linewidth and boosts the PLQY. The highly efficient light-emitting performance enables them as excellent down-conversion blue phosphors to fabricate solid-state LED giving bright warm white light with high color rendering index of 95.4. This work paves a novel structural optimization way to rationally design or fine-tune high-performance blue-light emitting halides. Graphical abstract: Highly efficient, ultrapure, and tunable blue-light emitting performances were realized in two new hybrid cadmium halides through structural evolution after synthesis techniques. By rationally controlling crystal rigidity and electron-quantum interaction as modulation strategy, synchronous optimization of emission efficiency and linewidth was achieved with optimal PLQY of 52.3% and color purity of 96.7%, which provides a novel structural optimization avenue to rationally design high-performance blue-light emitting perovskites. Image 1 Highlights: The tunable blue light-emitting performance was first achieved by crystalline structural conversion in hybrid cadmium halide. Synchronous optimization of emission efficiency and linewidth achieved with optimal PLQY of 52.3% and color purity of 96.7%. Crystal rigidifying strategy paves a new way to design high-performance blue-light emitting perovskites from the molecular level. Highly efficient and stable luminescence performance of LDHP show important potential in a solid-state light-emitting diode.